2020
DOI: 10.1111/jcmm.16040
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HCG11/miR‐26b‐5p/QKI5 feedback loop reversed high glucose‐induced proliferation and angiogenesis inhibition of HUVECs

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Thus, suppression of miR-214 expression may be a possible treatment for atherosclerotic CVDs. Other miRNAs, such as miR-26b-5p, miR-17-5p, and miR-181-5p, show inhibitory effects on TCF7L2 expression similar to those of miR-217 (122,123). Moreover, miR-26b-5p and miR-17-5p can promote adipogenic differentiation by downregulating TCF7L2 expression (124).…”
Section: Therapeutic Strategies To Promote Tcf7l2 Expressionmentioning
confidence: 93%
“…Thus, suppression of miR-214 expression may be a possible treatment for atherosclerotic CVDs. Other miRNAs, such as miR-26b-5p, miR-17-5p, and miR-181-5p, show inhibitory effects on TCF7L2 expression similar to those of miR-217 (122,123). Moreover, miR-26b-5p and miR-17-5p can promote adipogenic differentiation by downregulating TCF7L2 expression (124).…”
Section: Therapeutic Strategies To Promote Tcf7l2 Expressionmentioning
confidence: 93%
“…LINC00657 represses miR-26b-5p and enhances COMMD8 expression to promote NSCLC progression [ 27 ]. In addition, lncRNA HCG11 participates in the regulation of HUVEC proliferation by suppressing miR-26b-5p on QKI-5 expression [ 28 ]. These results support the idea that miR-26b-5p is implicated in the negative regulation of cell growth, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the main transcription products of QKI include QKi-5, QKi-6, and QKi-7, which have relatively conservative sequences, and the different sequences mainly exist in the C-terminal. These three QKI allosteric proteins all existed in vascular endothelial cells, and QKI-5 has the highest expression abundance [ 18 ]. Both QKI-5 and QKI-6 have a favorable impact on angiogenesis, but they play a different role in different cell types, showing the key influence of the unique C-terminal sequence on its function.…”
Section: Introductionmentioning
confidence: 99%